Pengaruh Fasilitas Kantor Terhadap Efektivitas Kerja Pegawai Pada Kantor Kecamatan Telutih Kabupaten Maluku Tengah - Rahma Wati Ilihelu; Fauzia Tutupoho; Chyntia Imelda Tjokro (P3M Politeknik Negeri Ambon, 2024)
Office facilities are a factor that influences and increases employee work effectiveness. This research aims to determine the influence of office facilities on employee work effectiveness at the Telutih District Office, Central Maluku Regency. The sample was taken from 32 respondents using the nonprobability sampling formula. The analytical method used in this research is simple linear regression analysis and descriptive analysis with SPSS software, the regression obtained is Y=0.675 + 0.789X, while descriptive analysis shows that office facilities at the Telutih District Office, Central Maluku Regency have an average value of 3 .19 which is interpreted as quite good, and work effectiveness shows that the average value is 3.33 which is interpreted as quite good. The research results show that the termination coefficient value for office facilities which influences employee work effectiveness has a contribution of 96.9% and the remaining 3.1% is influenced by other variables outside the research. Based on these results, it can be concluded that office facilities have a positive and significant effect on the work effectiveness of employees at the Telutih District Office, Central Maluku Regency. Keywords: Office Facilities, Work Effectiveness